ID: 77. Issue 1 (November 2015) - Witalisz-Siepracka, Agnieszka; Prchal-Murphy, Michaela; Bednarik, Karoline; Meissl, Katrin; Putz, Eva Maria; Gotthardt, Dagmar; Sexl, Veronika; Strobl, Birgit; Müller, Mathias
<x xml:space="preserve">Abstract</x> Tyrosine kinase 2 (TYK2) is a member of the Janus kinase (JAK) family. Loss of TYK2 reduces cytotoxicity of both natural killer (NK) and cytotoxic T cells (CTL) in tumour surveillance. In addition to the canonical cytokine receptor associated and enzymatic activities, JAKs function also non-canonical, i.e. kinase independent and/or scaffolding. Recently, hyperactive TYK2 has been assigned to leukaemia forms in humans and therefore TYK2 inhibitors emerge in cancer therapy. In order to assess the non-canonical functions of TYK2 and potential harmful effects of its inhibition on tumour surveillance we have gene-targeted mouse strain expressing kinase-inactive TYK2 (TYK2K923E). TYK2K923E partially restored the impaired maturation of splenic NK cells from Tyk2−/− mice. NK cell cytotoxicity against a range of target cells was significantly improved by TYK2K923E compared to loss of TYK2. IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pbb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> production after IL-12 or NK cell receptor stimulation was fully dependent on enzymatically active TYK2. Most importantly, the control of NK cell targeted transplantable tumours was governed by TYK2K923E. In contrast to NK cells, Tyk2K923E CTLs show fully impaired cytotoxicity but, surprisingly, Tyk2K923E mice were capable to limit the growth of T cell targeted transplantable tumours. Reconstitution experiments in Rag2−/− mice revealed that Tyk2K923E T cells induce NK cell tumour infiltration more efficiently than Tyk2−/− T cells, which we propose to enable tumour eradication. We are currently investigating the mechanisms underlying this T cell-NK cell crosstalk and the dependence on non-canonical TYK2. VS, MM and BS are supported by the Austrian Science Fund (FWF SFB-F28, and DK-W1212).